AL-MAQASID AL-SYARIAH REVIEW OF DIVORCE FINES IN NGAJU DAYAK TRADITIONAL MARRIAGE AGREEMENTS IN CENTRAL KALIMANTAN - Muhammad Yoga (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
As social creatures we cannot live without other people because we need each other. And it is predestined and created for humans to live in pairs in order to form a happy family, to pity each other, and to continue their offspring in the form of marriage. However, in practice, every family is faced with various challenges. It is not uncommon for problems in the family to cause divorce. One step to deal with this problem is to enter into a marriage agreement as a guide for husband and wife when problems arise, such as non-fulfillment of rights in the household. This research aims to 1) Find out the fines for divorce in Dayak Ngaju traditional marriage agreements in Central Kalimantan, 2) Find out what the fines for divorce in Dayak traditional agreements are from the perspective of Al-maqasid al-syari'ah. The type of research used in this research is descriptive qualitative research with a field research approach, library research and the data collection techniques used are library research, interviews, observation and documentation. The results of the research show that the fines for divorce in the Dayak Ngaju traditional marriage agreement in Central Kalimantan are: 1. Singer hatulanglum (fine for unilateral divorce), 2) Singer hatulang palekak sama handak (fine for wanting to be together). A review of the fines for divorce in the Dayak Ngaju traditional agreement in Central Kalimantan from the perspective of al-maqasid al-syari'ah, the marriage agreement in the UUP and KHI is in accordance with the concept of maqasid al-syariah which emphasizes not violating religious rules. The concept of maqasid al-syariah is to create benefits in accordance with Islamic law which is prescribed to realize the etiquette of maintaining human benefits which in family relationships is shown to form a happy family